P-Toluenesulfonic acid coated natural phosphate as an efficient catalyst for the synthesis of 2-substituted benzimidazole. (1st December 2018) - Belkharchach, Soumia; Elayadi, Hanane; Ighachane, Hana; Sebti, Said; Ali, Mustapha Ait; Lazrek, Hassan
2-Substituted benzimidazoles are selectively synthesised in high yields via the condensation of o-phenylenediamine derivatives with aldehyde derivatives using catalytic amount of p-toluenesulfonic acid coated natural phosphate (NP/PTSA) under mild conditions. The use of NP/PTSA as a reusable catalyst makes this process simple, convenient, and environmentally friendly.